Foveal-Sparing ILM Peeling with ILM Flap Transposition over the Macular Hole for Repair of Full-Thickness Macular Holes - Leisser, Christoph; Findl, Oliver (Klinische Monatsblätter für Augenheilkunde, 2024)
Background Full-thickness macular holes, defined as full-thickness defects of the fovea, lead to central scotoma and deterioration of vision. Apart from peeling of the internal limiting membrane (ILM), ILM flap techniques have been reported to have potential in improving results in macular hole surgery. In addition, foveal-sparing ILM peeling gives a high macular hole closure rate and improvement in postoperative visual acuity. The aim of this study was to examine outcomes in a cohort of patients with full-thickness macular holes that underwent vitrectomy with foveal-sparing ILM peeling and transposition of an ILM flap over the macular hole.Methods This retrospective study included patients scheduled for pars plana vitrectomy with foveal-sparing ILM peeling, combined with ILM flap transposition over the macular hole, for macular hole repair. All patients received a gas tamponade with 20% sulphur hexafluoride and were encouraged to undergo postoperative face-down positioning for 48 hours after surgery. Optical coherence tomography (OCT) imaging of the macula and distance-corrected visual acuity (DCVA) were performed before and 3 months after surgery.Results In total, 42 eyes of 42 patients were included in this study. Leaving a broad area of residual ILM at the foveal rim led to a high risk of failure in macular hole closure, while leaving a narrow zone of residual ILM at the foveal rim resulted in high macular hole closure rates (97% type 1 closure and 3% type 2 closure), with a median improvement of DCVA of 4 lines [interquartile range (IQR): 3 to 6] among pseudophakic and 3.5 lines (IQR: 2 to 5) among phakic patients.Conclusions A combination of foveal-sparing ILM peeling with ILM flap techniques was shown to be a safe and effective surgical option for patients with full-thickness macular holes, resulting in a high macular hole closure rate and improvement in visual acuity in the majority of patients.
Keywords: foveal-sparing ILM peeling; ILM flap transposition; full-thickness macular hole